IMPLIKASI BANTUAN OPERASIONAL SEKOLAH (BOS) BUKU TERHADAP KREATIVITAS GURU MENULIS BUKU MODUL - Isharijadi, Isharijadi (Jurnal Pendidikan, 2008)
ThisÂ  researchÂ  servesÂ  an analysisÂ  as to empiricallyÂ Â  explainÂ  the implementationÂ Â Â  of School Operational GrantÂ  (BOS)Â  for books from government andÂ  its relevanceÂ Â  towardsÂ  the teachers creativeness in writingÂ Â  booksÂ  andÂ  modules.Â Â  SchoolÂ  OperationalÂ Â  Grant Â for booksÂ  is intendedÂ Â Â  toÂ  easeÂ Â  studentsâ parentsÂ Â  inÂ  providingÂ Â Â  booksÂ Â  forÂ  their children.Teachers, as the front-liners for the students learning development, are attempted to creatively provide theÂ  sufficient learningÂ  resources, one of which is done byÂ  arrangingÂ Â Â  subject modules.Â Â Â  TheÂ Â  teachersÂ Â Â  areÂ  obligedÂ Â  forÂ  arrangementÂ Â Â  ofÂ  learning modules,Â Â  becauseÂ  throughÂ  the modulesÂ  they can renderÂ  creativeness and materialÂ Â  developmentÂ Â  for studentsÂ  basedÂ  on the developmentÂ Â  of theÂ  marketÂ  shareÂ  and lack of teachers works.UnderÂ  empiricalÂ  observationÂ  done by the researcher,Â  it is found that the School OperationalÂ  Grant for books arises dilemma for teachers and publicÂ  in terms thatÂ  1) teachersÂ  face difficultiesÂ  to distributeÂ  their works/modulesÂ Â  in substitutionÂ  for books from BOS, 2) the demandÂ  for teachersÂ Â Â  modulesÂ Â  and booksÂ  becomesÂ Â  studentsÂ Â  parentsÂ  burden,Â  3) the distributionÂ Â  of the grant books which needs veryÂ  strict supervision fromÂ  the authority.Key terms:Â  BOS for books,Â  teachersÂ Â  creativeness